Strategic situational planning and management of pharmaceutical services and supply: The experience of a municipality in the State of São Paulo with regard to optimizing spending on medicinal lawsuits (Brazilian Journal of Pharmaceutical Sciences, 2019)
One of the actions taken was to offer training on pharmaceuticals via the distance education model (EAD) with the course titled Pharmaceutical Services and Supply Management Course (PSSMC). PSSMC, which was based on the idea of expanded management, is guided by Strategic Situational Planning (PES) concepts, and structured around an Operational Plan (OP) that serves as a practical didactic tool. The aim of this study is to report and analyze a case study based on the implementation of the Operational Plan in a municipality in the State of São Paulo, while focusing on the judicialization of access to medicines and health products. Since judicialization is an important topic, the problem chosen for resolution with the PES was attendance at the issuance of court orders by the municipality for items of medium and high complexity. The PES allows researchers to analyze reality through different points of view, of which participation is a key aspect. With the OP, it was possible to disseminate a proposal for expanded planning, to advance resolution of the problem, achieve positive results, and reduce expenses associated with the municipality’s legal actions.